Application of core functions and forms in complex health intervention research: a scoping review protocol - Eunyoung Kang; Maria E Fernández; Jessica D Austin; Monica Perez Jolles; Katelyn Fox; Debbie Passey; Laura Zeigen; Erin Kenzie; Rachel J Meadows (BMJ Open)
Introduction The ability of healthcare, community and public health systems to effectively implement and disseminate research innovations depends on contextual factors at multiple interconnected levels of influence (eg, the innovation, individual, provider/implementor, organisation and health system). Recently, there has been an increase in the development of complex interventions designed to target multiple levels, designed for or adapted to the context in which they are delivered. Two concepts from complex systems thinking have been increasingly used to operationalise such interventions—core functions (theory and evidence-driven purposes of interventions) and forms (adaptable activities that perform each core function). However, there is a gap in the literature regarding how these concepts are being applied in intervention design and evaluation and implementation strategies. To fill this gap and advance understanding of complex health interventions, this scoping review will:Identify how functions and forms are defined and operationalised across complex health implementation research studies.Describe methodological approaches to identify or apply the concepts of core functions and forms to the design and evaluation of complex health interventions and implementation strategies.Methods and analysis This review will follow the methodological approach of Arksey and O’Malley. The search strategy will include electronic databases (PubMed, Scopus, Embase, CINAHL and Web of Science) and reference lists and citations of exemplar papers in the field. The literature search will be designed to capture research applying the concepts of core functions and forms in healthcare and public health complex interventions. The search will be restricted to studies published in English in peer-reviewed academic journals. Two coders will screen study titles and abstracts, followed by full-text reviews. One researcher will extract the data and a second will review it for any omissions or errors. An inductive content analysis will be used to categorise the nature of how studies define and operationalise core functions and forms. The scope of the work in this area and methodology (eg, measures selection and analytic approaches) will be described narratively. Results will be presented to experts in the field and their input will be used to further contextualise the findings.Ethics and dissemination This project does not require ethics approval. We will share the findings and data results will be shared via peer-reviewed journals.Trial registration number https://doi.org/10.17605/OSF.IO/YQFP7